TRANSNATIONAL IDENTITIES IN JHUMPA LAHIRIS FICTION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Transnationalism generates connections between people, societies, and nations, as well aschanges in the social, economic, and cultural lives of both the origin and destinationcountries. The purpose of this article is to look at the impact of people movement, technology,and trade on modern life, society, culture, and literature. It focuses on experiences thattranscend national, racial, and linguistic borders. "Someone who expands and goes beyondnational limits," Merriam Webster defines transnational as "someone who extends and goesbeyond national boundaries" (Webster). The prefix Trans, which means "across," "beyond,"and "outside of," is a Latin preposition. As a result, transnational refers to something thatexists outside of a nation. Nation is a word that comes from the Latin word natio and refersto an imagined polity that exists inside a defined territory. The modern-nation notion,according to Tölölyan, is unquestionably a product of the Enlightenment era, and it has nowtransformed due to population dispersal.